2022
DOI: 10.21608/aimj.2022.108415.1691
|View full text |Cite
|
Sign up to set email alerts
|

A comparison Between the Effect of Metformin and Progesterone on the Endometrium in cases of peri menopausal bleeding

Abstract: Users have the right to read, download, copy, distribute, print, search, or link to the full texts of articles under the following conditions: Creative Commons Attribution-Share Alike 4.0 International Public License (CC BY-SA 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…In group 2, the mean and SD for age was 48±2.15, 33.85±2.98 for BMI (kg/m2), 3.98±0.7 for gravidity and 3.3±1.2 for parity. Our study was agreed to Hussein et al; 2022 study [27] who showed that according to gravidity, a little difference was found between Metformin and Progesterone groups. Consistent with parity, no statistically significant variance was found between Metformin and Progesterone groups.…”
Section: Discussionsupporting
confidence: 93%
“…In group 2, the mean and SD for age was 48±2.15, 33.85±2.98 for BMI (kg/m2), 3.98±0.7 for gravidity and 3.3±1.2 for parity. Our study was agreed to Hussein et al; 2022 study [27] who showed that according to gravidity, a little difference was found between Metformin and Progesterone groups. Consistent with parity, no statistically significant variance was found between Metformin and Progesterone groups.…”
Section: Discussionsupporting
confidence: 93%